2006
DOI: 10.1007/s10531-005-3576-0
|View full text |Cite
|
Sign up to set email alerts
|

Home gardens in western Nepal: opportunities and challenges for on-farm management of agrobiodiversity

Abstract: Home gardens are defined as a system of production of diverse crop plant species, which can be adjacent to household or slightly further away and is easily accessible. Species composition and management systems of Nepalese home gardens are poorly known. The study was conducted to develop an inventory on composition of crop species and varietal diversity to characterise the home gardens of Rupandehi and Gulmi of western Nepal, and to observe the species change over the time for last 10-15 years. Semi-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
61
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 18 publications
(9 reference statements)
12
61
1
2
Order By: Relevance
“…It organises the irrigation calendar, decides the best period for spring and autumnal land preparation and in local market, as observed by other authors worldwide (e.g. Hoogerbrugge and Fresco 1993;Lok 2001;VoglLukasser 2003 andAlbuquerque et al 2005;Kumar and Nair 2004;Maroyi 2009;Shillington 2008;Sunwar et al 2006). Moreover, Montesinho homegardens had additional and unique characteristics related to the architecture of the settlements, local culture and gardeners' perceptions and strategies that defined the different types reported.…”
Section: Sampling and Data Collectionmentioning
confidence: 66%
See 1 more Smart Citation
“…It organises the irrigation calendar, decides the best period for spring and autumnal land preparation and in local market, as observed by other authors worldwide (e.g. Hoogerbrugge and Fresco 1993;Lok 2001;VoglLukasser 2003 andAlbuquerque et al 2005;Kumar and Nair 2004;Maroyi 2009;Shillington 2008;Sunwar et al 2006). Moreover, Montesinho homegardens had additional and unique characteristics related to the architecture of the settlements, local culture and gardeners' perceptions and strategies that defined the different types reported.…”
Section: Sampling and Data Collectionmentioning
confidence: 66%
“…Albuquerque et al 2005;Kumar and Nair 2004;Maroyi 2009;Shillington 2008;Sunwar et al 2006). Nevertheless, in Europe, particularly in the Iberian Peninsula, homegardens' research is quite recent and still limited (Reis-Garcia et al 2012).…”
Section: Study Area Backgroundmentioning
confidence: 99%
“…It would also facilitate increased involvement of women farmers in agriculture, required because of increasing out-migration of the male labor force. It is shown that the wells offer enough water storage for irrigating from 0.1 to 0.2 ha of land, which is larger than an average home garden in Rupandehi District [18]. This potential can be further enhanced by implementing more efficient irrigation systems especially through promotion of home gardening, which could result in increased production and consumption, thereby enhancing family nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Rainfall (Figure 6), temperature (Figure 7), relative humidity ( Figure 8) and wind speed ( Figure 9) were obtained for Bhairahawa Agricultural Station Index 707 [16][17][18][19]. The CROPWAT program was then used to estimate the reference crop evapotranspiration ( Figure 10) for the study location based on the climatological data collected at Bhairahawa Agricultural Station.…”
Section: Irrigation Water Requirementmentioning
confidence: 99%
“…Some of the important researches on in situ conservation of agrobiodiversity and its role on conservation of plant genetic resources are Agelet et al (2000), Sunwar et al (2006), Perrault-Archambault and Coomes (2008), Calvet-Mir et al (2011), etc. Previous researchers have highlighted the importance of seed exchange in the home-gardens as conservation of plant germplasm (Calvet-Mir et al, 2012).…”
Section: Introductionmentioning
confidence: 99%